Annulated Heterocyclic Derivatives of 1, 3, 6, 8‐Tetraazapyrene. Issue 24 (1st July 2013) - Martens, Susanne C.; Hahn, Lena; Lombeck, Florian; Rybina, Arina; Wadepohl, Hubert; Gade, Lutz H.
Abstract: Polyheterocyclic aromatic compounds combining the electron‐poor 1, 3, 6, 8‐tetraazapyrene (TAPy) unit with electron‐rich heterocycles are reported. They were obtained as side‐products from the reaction of the tin "double salt" of tetraaminonaphthalene hydrochloride with trifluoroacetic anhydride in pyridine. Apart from the target product, 2, 7‐bis(trifluoromethyl)‐1, 3, 6, 8‐tetraazapyrene (1 ), several novel heteroaromatics were obtained resulting from the annulation of a furan (2 ) or indolizine unit (3 ) to the TAPy core. Upon recrystallization from methanol, methanol added to compound2 to yield the racemate of the homochiral diastereomer [( R, R )‐ and ( S, S )‐2a ]. Compound3 is strongly fluorescent ( φ = 0.68 in toluene) and the emission spectra display a significant bathochromic shift with increasing solvent polarity. The HOMO of3 is located on the indolizine part of the molecule, whereas the LUMO primarily resides on the tetraazapyrene unit, which suggests considerable intramolecular charge transfer in the corresponding π*←π transition. Abstract : Polycyclic heteroaromatics resulting from the annulation of a furan (left) or indolizine unit (right) to the 1, 3, 6, 8‐tetraazapyrene core have been obtained as side‐products from the reaction of the tin "double salt" of tetraaminonaphthalene hydrochloride with trifluoroacetic anhydride in pyridine.